Editorial - Armstrong , Anona (Journal of Law and Governance, 2015)
This issue of the Journal presents a second eclectic mix of papers from the Governance and Law Conference ranging from a paper concerning the legal issues of piercing the corporate veil, to three papers studies of small business finance, to strategic decisions about the factors affecting investment. It concludes with a paper which addresses the governance issues in the not-for profit sector through the governance of superannuation funds.